If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2a + -9 = 36 Reorder the terms: -9 + -2a = 36 Solving -9 + -2a = 36 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -2a = 36 + 9 Combine like terms: -9 + 9 = 0 0 + -2a = 36 + 9 -2a = 36 + 9 Combine like terms: 36 + 9 = 45 -2a = 45 Divide each side by '-2'. a = -22.5 Simplifying a = -22.5
| 42m^3-36m^2-49m+42=0 | | 8x^2+5x+k=0 | | y^2+33=-8x-23 | | 3x^2+16x=-21 | | (n+11)n=84 | | 3=-16t^2+19t+0 | | 54a^2-144a=0 | | 2x^2-42=8 | | 2+3(n-6)=4(n+2)-21 | | 20x-8-12x+3=21x-9-13x+14 | | 15(-4g+8)+6=-1-(9-8g) | | 5p+14=8p(-2) | | 60n^2+258n+168=0 | | 2X^3-3X^2-3=0 | | 5.3x-3.24=3.18-5.4x | | 5p+14=8p-(-2) | | -3x+3=-33 | | 2.1x-5.25=3.15-3.5x | | 9x+7=6x+8 | | 2.1x-5.25=3.15-3.5 | | -7x-12+20x=14-12x+25x-10 | | 5x^2+46x-40=0 | | 3n+7=5n+3 | | 9x+5y=11x-8y | | 3x-5+1=-2x+7 | | 7+9(x-3)=1-6(x-9) | | 9y+5x=11y-8x | | 6y+5=11y+30 | | (-12a)(ab)=0 | | 18x^2-72x+40=0 | | (-12abc)(4ab)=0 | | 2(x-5)=-10+2x |